GLOBAL WARMING ISSUE AWARENESS THROUGH VIDEO GAME DESIGN: AN IMPLEMENTATION OF MDA FRAMEWORK - Tony Wibowo; Mega Lispy (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
The popularity of video games among younger generation today is undeniable. Video games can be used in various purpose beyond mere entertainment value, one of which is delivering message in a more immersive manner than other linier media. Global warming is an issue that are currently becoming very complex and impactful to our daily lives. However, the solution of that problem is rather simple, one of which is forestation. This problem can be turned into video game mechanics to help player understand the urgency of the matter. in this study, we have designed a video game about global warming using the MDA framework method. We produced game design document which consists of mechanics, dynamics and aesthetics. This document then will be used as part of video game development. By designing this video game, we are attempting to spread the message of global warming to younger generation